Analytical fracture mechanics - Unger, David J. (Academic Press, 1995)
Fracture mechanics is an interdisciplinary subject that predicts the conditions under which materials fail due to crack growth.It spans several fields of interest including: mechanical, civil, and materials engineering, applied mathematics and physics.